2013
DOI: 10.1037/lat0000006
|View full text |Cite
|
Sign up to set email alerts
|

Familismo, ethnic identity, and bicultural stress as predictors of Mexican American adolescents’ positive psychological functioning.

Abstract: Through the use of the cultural-ecological-transactional theory of resilience, the present study seeks to determine if the cultural factors of familismo and ethnic identity have a protective effect and if bicultural stress has a risk effect on the positive psychological functioning of 191 Mexican American adolescents. Two hierarchical linear regressions were preformed to determine the direct and interaction effects of these factors on self-esteem and life satisfaction. Results indicate that familismo values an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 60 publications
4
94
0
Order By: Relevance
“…This model postulates constant interaction of sociocultural factors at the individual level, thus playing a proximal role. As (Piña-Watson et al 2013) explain, through the use of this model, cultural processes that children experience can be accounted for in a way that reflects dynamic and proximal relationships between the different component systems. Kuperminc et al (2009) asserted that issues of minority status in countries such as those analyzed here, i.e., socioeconomic stratification, gender roles, immigration status, language spoken in the home and the socially assigned value of education, were determinants of the context in which children live.…”
Section: A Model Of Educational Resiliencementioning
confidence: 99%
“…This model postulates constant interaction of sociocultural factors at the individual level, thus playing a proximal role. As (Piña-Watson et al 2013) explain, through the use of this model, cultural processes that children experience can be accounted for in a way that reflects dynamic and proximal relationships between the different component systems. Kuperminc et al (2009) asserted that issues of minority status in countries such as those analyzed here, i.e., socioeconomic stratification, gender roles, immigration status, language spoken in the home and the socially assigned value of education, were determinants of the context in which children live.…”
Section: A Model Of Educational Resiliencementioning
confidence: 99%
“…This finding suggests that as the amount of familism increases, the level of subjective happiness increases. Other researchers also have found that family values and support influenced life satisfaction among Latina/o high school students (Pina‐Watson et al, ) and adolescents (Edwards & Lopez, ) as well as among Mexican American adolescents (Pina‐Watson et al, ; Vela, Lenz, et al, ). Perceived family support and support from others also predicted happiness for immigrant women in Spain (Dominguez‐Fuentes & Hombrados‐Mendieta, ).…”
Section: Discussionmentioning
confidence: 88%
“…A sample response item is “My family is always there for me in times of need.” Reliability coefficients for scores on the total scale were measured in previous samples using coefficient alpha. Pina‐Watson, Ojeda, Castellon, and Dornhecker () found an alpha of .87 in a study regarding Mexican American adolescents’ positive psychological functioning. The internal consistency of this scale in the current study was .83.…”
Section: Methodsmentioning
confidence: 99%
“…This finding suggests that as the amount of familism increases, the level of subjective happiness increases. Pina‐Watson et al () found that family values and support influenced Latina/o high school students' life satisfaction. Edwards and Lopez () noted that family support had an impact on Mexican American adolescents' life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability coefficients for scores on the total scale were measured in previous samples by using coefficient alpha. Other researchers reported acceptable internal reliability (α = .87; Pina‐Watson et al, ). The internal consistency of this scale in the current study was .91.…”
Section: Methodsmentioning
confidence: 95%